Distribución de los esfuerzos en tres tipos de elementos intrarradiculares con diferentes longitudes (2008)
ABSTRACT: The purpose of this study was to observe the stress distribution of teeth restored with intraradicular retention elements (posts) of different lengths, using the finite element analysis (FEA). Methods: a tridimensional model of finite elements (4mm model with 34010 nodes and 9317 elements, 6 mm model with 36798 nodes and 10371 elements, 8 mm model with 38587 nodes and 11025 elements) of an upper central incisor is presented. The model of the dowel restored tooth involved trabecular bone, cortical bone, periodontal ligament, gingiva, root, gutta-percha, resin luting cement, posts, composite resin core (for prefabricated posts), metallic posts and metal ceramic crown. The dowels were fabricated with noble metal casting alloy, titanium and fiber glass. The dowels were cemented with resin luting cement. The variables included were modulus of elasticity, Poisson´s ratio, and post’s length (4, 6 and 8 mm). A load of 1N was applied to the crown at an angle of 45 degrees; von Mises stresses, main maximum and minimum stresses, maximum shear stress were then calculated. Results: finite element analysis indicated that the distribution of stresses generated on the modeled tooth with different post lengths decreased significantly, this is in agreement with an inverse proportional relationship with the material’s modulus of elasticity. Stresses on the root were also reduced when post length was increased (4, 6 and 8 mm). Conclusions: within the limitations of this study, it was found that strong variations exist with respect to the post length in relation with the stress distribution on the dentin and in the post itself, being less the distribution of stresses in the dentin and in the posts with more length and with a higher modulus of elasticity.